2021
DOI: 10.1371/journal.pntd.0009768
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated infection by a Pteropine orthoreovirus isolated from an Egyptian fruit bat in Zambia

Abstract: Background Pteropine orthoreovirus (PRV) is an emerging bat-borne zoonotic virus that causes severe respiratory illness in humans. Although PRVs have been identified in fruit bats and humans in Australia and Asia, little is known about the prevalence of PRV infection in Africa. Therefore, this study performed an PRV surveillance in fruit bats in Zambia. Methods Egyptian fruit bats (Rousettus aegyptiacus, n = 47) and straw-colored fruit bats (Eidolon helvum, n = 33) captured in Zambia in 2017–2018 were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…3 ). For the NBVs, previous studies demonstrated that bats ( 7 13 ), monkeys ( 14 ), and humans ( 15 21 ) were corroborated to carry this virus group. The current study successfully isolated two novel NBVs from blood-sucking bat flies ( Eucampsipoda sundaica ) on the body surface of bats.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3 ). For the NBVs, previous studies demonstrated that bats ( 7 13 ), monkeys ( 14 ), and humans ( 15 21 ) were corroborated to carry this virus group. The current study successfully isolated two novel NBVs from blood-sucking bat flies ( Eucampsipoda sundaica ) on the body surface of bats.…”
Section: Discussionmentioning
confidence: 93%
“…Since the discovery of NBV, more and more strains have been discovered in Asia and Africa. Among these, Pulau reovirus ( 8 ), Xi River reovirus ( 9 ), Cangyuan orthoreovirus ( 10 ), and Kasama virus ( 11 ) have been discovered only in bats, Pteropine orthoreovirus was discovered in both bats ( 12 , 13 ) and monkey feces ( 14 ), and Melaka orthoreovirus ( 15 ), Kampar orthoreovirus ( 16 ), and Pteropine orthoreovirus ( 17 21 ) were discovered in patients with respiratory or enteric diseases. Epidemiological investigation of these cases suggests that these human-associated NBVs can be transmitted among humans ( 15 , 20 , 21 ), and the causative viruses may be bat-originated because some patients were exposed to bats prior to disease onset ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reported seroprevalence of PRV in fruit bats is remarkably high, estimated between 63% and 90% 14 . The recent discovery of PRV in fruit bats in Africa markedly expands the geographic range of this zoonotic virus and warrants further surveillance for PRV in humans and bats 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…14 The recent discovery of PRV in fruit bats in Africa markedly expands the geographic range of this zoonotic virus and warrants further surveillance for PRV in humans and bats. 15,16 Although the increased understanding of PRV distribution over the years, the etiologic role of PRV in causing ARI remains poorly understood in ambulatory care settings, as previous studies were mostly conducted among outbreak patients who had recent exposures to bats in rural areas. Therefore, this study aims to assess the molecular prevalence, epidemiology, in vitro characteristics and the genetic diversity of PRV among patients with ARI in an urban population in Kuala Lumpur, Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…20,[51][52][53][54][55][56] .このうち,インドネシア にて採取したコウモリの脾臓から分離した新規ヘルペスウ 図 2 RVA ZFB14-135 株を検出した Ndola と RVA BatLi08 株が検出された Limbe の位置とストローオオコウモリ ( 株,ウシ由来 RVA 株に高い感受性を示した 60) .加えて, 培養細胞を用いた RVA 臨床株の増殖はトリプシンを添加 し た 無 血 清 培 地 下 で 実 施 す る 必 要 が あ る が,MA104-T2T11D 細胞ではトリプシンが失活する FBS 含有培地下 においても RVA が増殖することから,本細胞がウイルス 図 3 ICTV によって規定されるウイルス科(左)とウイルス種(右)総数の推移 47) pp.79-86,2022〕 Wang X, Zheng XS, Zhao K, Chen QJ, Deng F, Liu LL, Yan B, Zhan FX, Wang YY, Xiao GF, Shi ZL. A pneumonia outbreak associated with a new coronavirus of probable bat origin.…”
unclassified